Canadian hospitality law / Donald Longchamps, Bradley H.Wright - Donald, Longchamps
The first rule of hospitality law: do not enter into any agreement or relationship having legal consequences without first consulting a lawyer. For those player in the hospitality industry-owners, managers, employees, guests, and patrons-a defensive approach to the law pays dividends. In this book, we shall try to provide readers with the knowledge and skills that will enable them to better protect themselve and their businesses from negative legal experiences.